Prescribing errors at an academic teaching hospital in Johannesburg - Vally, Muhammed (My University, 2017)
Prescribing errors are considered the most preeminent error in medicine and currently there have been no South African published studies which investigated the occurrence and types of prescribing errors in our hospitals. Aims To classify and determine the occurrence of medication prescribing errors in selected ward prescriptions in an academic teaching hospital in Johannesburg. In addition to determine the reasons why these errors occur. Methods This study was a mixed methods study that first investigated prescribing error using a retrospective chart review in four wards (medical, surgical, psychiatric and paediatric wards) over a period of two consecutive months. The second part of the study involved using focus groups to determine the systems factors that led to errors taking place in the hospital. Results The adult prescribing error percentage was calculated at 17.9% and the paediatric error rate was 31.8%. There was a statistically significant difference in the error rate between the medical ward and others with an error rate of 19.97% in the medical ward, 13.28% in the surgical ward, 17.48% in the psychiatric ward and 31.80% in the paediatric ward. Clear systems factors such as lack of supervision, long working hours, lack of clinical pharmacology training and even lack of prescriber feedback were present that lead to errors taking place. Conclusions This was the first study in South Africa to compare four wards and to report on adult and paediatric prescribing errors. There were clear systems factors that could be linked to prescribing errors taking place and recommendations to reduce prescribing errors in the hospital are made.
A dissertation submitted to the School of Therapeutic Sciences, Faculty of Health Sciences , University of the Witwatersrand in fulfillment of the requirements for the degree of Master of Science in Medicine (Pharmacology) Johannesburg October 2017
Keywords: Medication Errors